2006
DOI: 10.1055/s-2005-872966
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Food Restriction Effects on Oxidative Stress in Judo

Abstract: We examined the effects of weight loss induced by restricting energy and fluid intake on antioxidant status and oxidative stress of judo athletes. Twenty male judoka were randomly assigned to one of two groups (Group A: called diet, n = 10; height 174.8 +/- 1.9 cm, body weight 75.9 +/- 3.1 kg; they were asked to lose approximately 5 % of their body weight through self-determined means during the week before the competition; Group B: called control, n = 10; height 176.4 +/- 1.1 cm, body weight 73.3 +/- 6.3 kg m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
43
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 36 publications
10
43
0
8
Order By: Relevance
“…Less information is available on anaerobic exerciseinduced oxidative modifications, as in judo (Finaud et al 2006). Groussard et al (2003) indicated that high-intensity anaerobic work resulted in oxidative modification of the above-mentioned macromolecules in both skeletal muscle and blood.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Less information is available on anaerobic exerciseinduced oxidative modifications, as in judo (Finaud et al 2006). Groussard et al (2003) indicated that high-intensity anaerobic work resulted in oxidative modification of the above-mentioned macromolecules in both skeletal muscle and blood.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study (Degoutte et al 2003), we reported that a judo training session, which included a warm-up, randori and a 5-min judo match carried out in competitive conditions, induced a high energetic demand similar to the levels evaluated after judo competition (Sikorski et al 1987). Evaluating the influence of dietary supplementation and exercise on oxidative stress would be very useful, particularly in judo, as competitors wrestle for a mean total of five 5-min bouts interspersed with 30-min seated recovery periods, which induces high levels of oxidative stress (Finaud et al 2006). Kraemer et al (2001) also investigated the performance and physiological responses to consecutive days of wrestling in a tournament format after a period of caloric restriction and thermal-and dehydration-induced weight loss.…”
Section: Introductionmentioning
confidence: 98%
“…Geralmente, essa estratégia inadequada deve-se ao fato de os atletas de combate precisarem manter ou reduzir um determinado peso corporal até a competição. Além disso, existe um agravo factual por procedimentos de restrição do consumo alimentar, desidratação e uso indevido de medicamentos 9,21 . Nesse sentido, a avaliação de fatores por nós não controlados, tais como a alimentação, uso de suplementos e medicamentos são fatores que podem modular as respostas das variáveis investigadas no presente estudo.…”
Section: Discussionunclassified
“…Além disso, houve diminuição na glicose em jejum, nos triglicérides, na pressão sistólica e diastólica e na frequência cardíaca (PAhL et al, 1988). A elevação na concentração de ácido úrico também foi obtida em um trabalho com judocas, bem como a diminuição significativa dos ácidos graxos livres e triglicérides (FINAUD et al, 2006). Após acompanhamento de 11 judocas de nível nacional, com restrição energética durante 7 dias e decréscimo significativo de 4,9 ± 1,2% do peso corporal, foram observadas elevações significativas nos níveis de triglicérides e ácidos graxos livres (FILAIRE et al, 2001).…”
Section: Revisão De Literatura Efeitos Fisiológicosunclassified